Near-dry wire-cut electrical discharge machining process using water–air-mist dielectric fluid: An experimental study. (2022) - Boopathi, Sampath; Anton Savio Lewise, K.; Subbiah, Ram; Sivaraman, G.
Abstract: In this paper, Inconel 600 alloy has been cut by water-mist wire-cut electrical discharge machining (WEDM) using a molybdenum wire tool. A little amount of tap water mixed with pressurized air (water-mist) was used to provide the dielectric insulation medium in the plasma zone. A new experimental arrangement has been made to conduct the near-dry WEDM using input parameters of the Current (K), Pulse-duration (PD), Pulse-pause time (PP), and flow rate (FR) of mixing tap water to predict the cutting speed (CS) and surface irregularity (SI). It was discovered that pulse-duration and current increase the CS and SI; conversely, the PT minimizes the CS and SI. The highest CS and SI are achieved by the highest flow rate of the tap water due to the quick flushing of debris. The percentage of contributions of K, PD, PP, and FR on CS is 20.94%, 22.22%, 47.86%, and 8.97% respectively and the percentage of contributions of K, PD, PP, and FR on SI is 17.06%, 39.1%, 26.50 %, and 17.34% respectively.